Drought Effects on Growth, Water Content and Osmoprotectants in Four Olive Cultivars with Different Drought Tolerance. Issue 3 (3rd July 2018) - Karimi, Soheil; Rahemi, Majid; Rostami, Ahmad Ali; Sedaghat, Sahar
ABSTRACT: This study investigates the growth and leaf composition of 2-year-old olive trees (Persian cultivars: Fishomi and Dezful and Greek cultivars: Amigdalolia and Conservolia) in response to withholding irrigation for 30 days under a hot and dry environment. Drought stress limited stem elongation, stem diameter expansion, formation of new leaves, leaf area, and specific leaf weight of the plants. However, the effect of drought on inhibition of growth of 'Fishomi' plants was higher than the other cultivars. 'Dezful', 'Amigdalolia' and 'Conservolia' were able to preserve higher levels of leaf relative water content and membrane stability index under drought stress. Higher drought tolerance of these plants was related to higher concentration of soluble carbohydrates, proline, potassium, and calcium in their leaves.